Multi-Attribute Decision Making Seleksi Kandidat Ketua OSIS Menggunakan Metode SMART - Chyntia Adelia Valentina Haris; Yesi Meliyana; Erna Novita; Dyah Ayu Megawaty (Journal of Data Science and Information Systems, 2023)
The selection process for candidates for Student Council President (Intra-School Student Organization) often involves various problems that need to be considered and overcome. There is a risk of non-objectivity in the assessment of candidates, either from the part of the selection committee or from the selection participants themselves. The purpose of this study is to apply the Simple Multi-Attribute Rating Technique (SMART) method in the selection of Student Council President candidates by the student affairs department before voting by students. The ranking results of candidates for student council president recommended 1st place with a final score of 0.738 with the name of the prospective candidate, Janice Lie, and 2nd place with a final score of 0.643 with the name of the prospective candidate, Branden Riski Dwi Kurniawan. Based on the application of the SMART method, 2 candidates for student council president are Janice Lie, and Branden Riski Dwi Kurniawan to carry out the next process in voting for the student council president election by the school students.